Frugivory and seed dispersal by tapirs: an insight on their ecological role - O'Farrill, Georgina; Galetti, Mauro [UNESP]; Campos-Arceiz, Ahimsa (Wiley-Blackwell, 2013)
Tapirs are one of the last extant megafauna species that survived the Pleistocene extinctions. Given their size and digestive system characteristics, tapirs might be the last potential seed disperser of plant species that were previously dispersed by other large mammal species that are now extinct. We compiled evidence from 39 published scientific studies showing that tapirs have a key role as seed dispersers and seed predators. Tapirs play an important role either through seed predation or by facilitating the recruitment of seeds over long distances, therefore influencing the diversity of plant species in the ecosystem. Neotropical tapirs might have a unique role as long-distance seed dispersers of large seeds (<20 mm) because they are capable of depositing viable large seeds in favorable places for germination that even large-bodied primates cannot disperse. Given the high diversity of seed species found in tapir diet, more information is needed on the identification of seed traits that allow the survival of seeds in the tapir's gut. Moreover, further studies are necessary on the role of tapirs as seed dispersers and predators; in particular considering spatial patterns of dispersed seeds, seed viability, effect of dung, and seed density in tapir latrines, and the effect of deposition sites on germination and seedling survival. Because all tapir species are highly threatened, it is paramount to identify gaps in our knowledge on the ecological role of tapirs and, in particular, on critical and endangered plant-tapir interactions to avoid possible trophic cascading effects on ecosystem function.
Keywords: defaunation; ecological function; long-distance dispersal; megafaunal dispersal syndrome; trophic cascades